Materialising the Future A Learning Path to Understand, Develop and Apply Emerging Materials and Technologies - Ferraro, Venere; Kääriäinen, Pirjo; Morer-Camo, Paz; Pasold, Anke (Research for Development, 2023)
This open access book offers a host of theoretical knowledge at the basis of new EM&Ts (namely, Interactive Connected Smart Materials, Wearables (ICS), Nanomaterials, Advanced Growing Materials, and Experimental Wood-Based Materials), as communicated through the unique design teaching method developed within the context of the European Project DATEMATS, a result of the creative workshops held by the four higher education institutions that were partners in the project, stressing the pros and cons of the method and offering ideas for further development and improvement. The modern age requires its own innovations in regards to both social and industrial progress, innovations made possible by Emerging Materials and Technologies (EM&Ts). Frameworks for designing both with and for the new materials are presented, educating designers about the opportunities offered by EM&Ts and how to take advantage of them. At the same time, the book explains how the method developed through the knowledge generated at research centers and universities can be communicated to companies across various industries that stand to gain from it, linking the assorted stakeholders, and includes a final chapter based on feedback from both students and business professionals as to the benefits of academic/industrial cooperation. This is an open access book.